Carrion's Disease - Takano Morón, Juan (1995)
The human Bartonellosis history Iinked to the exploit of Daniel A. Carrion, a 6th year student of the Faculty of Medicine from UNMSM is analysed on the basis of technological advances and progressive resolutions of different inquiries in the knowledge of the disease.